2013
DOI: 10.1007/s00015-013-0153-5
|View full text |Cite
|
Sign up to set email alerts
|

The structural history of the Mont Blanc massif with regard to models for its recent exhumation

Abstract: The tectonic evolution of the Mont Blanc range with regard to its cooling and exhumation history has been discussed and debated over many years and is still controversial. Recently, several low-temperature thermochronology studies have determined the cooling history of the massif in considerable detail and various tectonic models proposed to explain the young and fast exhumation signal established from these studies. Here we present detailed field data from the wider Mont Blanc area and assess possible exhumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 46 publications
(66 reference statements)
1
42
0
Order By: Relevance
“…The mechanism and amount of reactivation of the Jurassic normal faults are still debated (Bellahsen et al, , ; Gidon, ; Gillcrist et al, ). The Alpine deformation of these basement windows is generally weak and heterogeneous (Figure ), with a gradient of deformation increasing from NW to SE (Aar‐Gotthard: Berger et al, ; Choukroune & Gapais, ; Marquer, ; Mont Blanc: Egli & Mancktelow, ; Leloup et al, ; Rolland et al, ; Grand Châtelard: Marquer et al, ). The pre‐Triassic basement is affected by subgreenschist‐ to greenschist‐facies shear zones of Oligocene age (Cenki‐Tok et al, ; Egli et al, , ) predating the major (Miocene) phase of exhumation due to the initiation of frontal crustal ramps below the External Massifs (Boutoux et al, ).…”
Section: Geological Settingmentioning
confidence: 99%
“…The mechanism and amount of reactivation of the Jurassic normal faults are still debated (Bellahsen et al, , ; Gidon, ; Gillcrist et al, ). The Alpine deformation of these basement windows is generally weak and heterogeneous (Figure ), with a gradient of deformation increasing from NW to SE (Aar‐Gotthard: Berger et al, ; Choukroune & Gapais, ; Marquer, ; Mont Blanc: Egli & Mancktelow, ; Leloup et al, ; Rolland et al, ; Grand Châtelard: Marquer et al, ). The pre‐Triassic basement is affected by subgreenschist‐ to greenschist‐facies shear zones of Oligocene age (Cenki‐Tok et al, ; Egli et al, , ) predating the major (Miocene) phase of exhumation due to the initiation of frontal crustal ramps below the External Massifs (Boutoux et al, ).…”
Section: Geological Settingmentioning
confidence: 99%
“…Several studies on the exhumation history of the External Crystalline Massifs of the Western Alps (Argentera: Bigot-Cormier and others, 2006;Pelvoux: van der Beek and others, 2010;Mont Blanc: Leloup andothers, 2005 andothers, 2008), indicate a three stage evolution: First, exhumation rates peaked at around 6 to 7 Ma, dropped by an order of magnitude later on, only to finally increase again during the Plio-Quaternary to values around 0.5 to 1 km/Myr. Egli and Mancktelow (2013) showed that none of the major faults or shear zones directly bounding the Mont Blanc massif were actively accommodating vertical motion in Late Neogene times and that young exhumation is therefore not controlled by these structures. This most recent and final increase in exhumation rate has been explained by recent valley carving in response to glacial erosion (Leloup and others, 2005;Glotzbach and others, 2008;Valla and others, 2011).…”
Section: Plio-pleistocenementioning
confidence: 99%
“…The tectonic setting of the Rhône Basin is dominated by the Rhône-Simplon fault system, where dextral strike-slip movements since early Miocene times have accommodated most of the orogenic extension (Schlunegger and Willett, 1999;Egli and Mancktelow, 2013). Seward and Mancktelow (1994) suggested that faulting also had a normal slip component, which played an important role in the younger exhumation history of the area.…”
Section: Tectonicsmentioning
confidence: 99%